Analysis of performance of in-situ carbon steel bar reinforced Al-alloy foams. (15th September 2016) - Duarte, Isabel; Krstulović-Opara, Lovre; Vesenjak, Matej
Abstract: This paper presents results of an experimental study on the processing and mechanical characterisation of plain and in-situ carbon-steel bar reinforced cylindrical Al-alloy foams. The reinforcement is incorporated into the foam-structure during the foaming-process which is based on the powder metallurgy method. Some key technical issues concerning the manufacturing procedure are discussed. A technical solution to design moulds to prepare high-quality foam parts with longer lengths is proposed. This has been achieved by constructing moulds with varied mould-wall thickness. Such an approach enabled to control the foaming-process and subsequent the foam-filling in different regions of the mould cavity. A series of plain and in-situ reinforced foams with two different lengths (150 and 200 mm) and the same diameter (25 mm) were fabricated. Uniaxial compressive and three-point bending behaviour was studied, exploring their deformation and failure mechanisms. The results demonstrate that the carbon-steel bar increases the compressive behaviour of the foams but does not significantly influence their bending behaviour in terms of peak load. Under bending loads, the stress–strain curves are shifted along the strain axis in comparison to the plain foams. The deformation and failure mode of both specimens under compressive and bending loads is similar. The results indicate the potential of reinforced materials.